2016
DOI: 10.1111/pan.12936
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anesthetic agents on otoacoustic emissions in children: propofol vs ketamine

Abstract: DPOAE measurements were reduced similarly by propofol and ketamine anesthesia. Lower false outcome ratio in TEOAE measurements made propofol a better option than ketamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Propofol is a short‐acting intravenous anaesthetic reagent that is widely used for sedation and hypnosis during and after operation . It has advantages over other anaesthetic drugs by protecting the immune system from being inhibited, and neuron cells from oxidative stress and hypoxia injury .…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is a short‐acting intravenous anaesthetic reagent that is widely used for sedation and hypnosis during and after operation . It has advantages over other anaesthetic drugs by protecting the immune system from being inhibited, and neuron cells from oxidative stress and hypoxia injury .…”
Section: Introductionmentioning
confidence: 99%
“…Propofol is a general sedative reagent and commonly used for induction and maintenance of general anesthesia [ 9 ]. It has advantages over other anesthetic drugs by protecting neuron and endothelial cells from oxidative stress and hypoxia injury [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining OAEs under sedation was recommended, especially in severe ASD children, to control motor issues that may interfere with OAE testing (Tas et al, 2017). However, Gungor et al, 2016 observed a significant reduction in DPOAE levels with sedative agents.…”
Section: Discussionmentioning
confidence: 85%